The K12 beamline for the KLEVER experiment. (November 2019) - van Dijk, M W U; Banerjee, D; Bernhard, J; Brugger, M; Charitonidis, N; D'Alessandro, G L; Doble, N; Gatignon, L; Gerbershagen, A; Montbarbon, E; Moulson, M; Rae, B; et al.
Abstract: The KLEVER experiment is proposed to run in the CERN ECN3 underground cavern from 2026 onward. The goal of the experiment is to measure BR ( K L → π 0 v v ¯ ), which could yield information about potential new physics, by itself and in combination with the measurement of BR ( K + → π + v v ¯ ) of NA62. A full description will be given of the considerations in designing the new K12 beamline for KLEVER, as obtained from a purpose made simulation with FLUKA. The high intensities required by KLEVER, 2 × 10 13 protons on target every 16.8 s, with 5 × 10 19 protons accumulated over 5 years, place stringent demands on adequate muon sweeping to minimize backgrounds in the detector. The target and primary dump need to be able to survive these demanding conditions, while respecting strict radiation protection criteria. A series of design choices will be shown to lead to a neutral beamline sufficiently capable of suppressing relevant backgrounds, such as photons generated by π 0 decays in the target, and Λ → nπ 0 decays, which mimic the signal decay.